Inactivation of the MAPK signaling pathway by Listeria monocytogenes infection promotes trophoblast giant cell death - Hashino, Masanori; Tachibana, Masato; Nishida, Takashi; Hara, Hideki; Tsuchiya, Kohsuke; Mitsuyama, Masao; Watanabe, Kenta; Shimizu, Takashi; Watarai, Masahisa (Frontiers in Microbiology, 2015)
Listeria monocytogenes has a well-characterized ability to cross the placental barrier, resulting in spontaneous abortion and fetal infections. However, the mechanisms resulting in infection-associated abortion are not fully understood. In this study, we demonstrate that the dephosphorylation of MAPK family proteins caused by L. monocytogenes infection of trophoblast giant (TG) cells, which are placental immune cells, contributes to infectious abortion. Dephosphorylation of c-Jun, p38, and ERK1/2 was observed in infected TG cells, causing the downregulation of cytoprotective heme oxygenase (HO)-1. Blocking the dephosphorylation of proteins, including MAPK family proteins, inhibited the decrease in HO-1 expression. Treatment with MAPK inhibitors inhibited bacterial internalization into TG cells. Moreover, Toll-like receptor 2 involved in the expression of MAPK family proteins. Infection with a listeriolysin O-deleted mutant impaired dephosphorylation of MAPK family proteins in TG cells and did not induce infectious abortion in a mouse model. These results suggest that inactivation of the MAPK pathway by L. monocytogenes induces TG cell death and causes infectious abortion.